Nuclear carrier and RNA‐binding proteins in frontotemporal lobar degeneration associated with fused in sarcoma (FUS) pathological changes. Issue 2 (25th January 2013) - Davidson, Y. S.; Robinson, A. C.; Hu, Q.; Mishra, M.; Baborie, A.; Jaros, E.; Perry, R. H.; Cairns, N. J.; Richardson, A.; Gerhard, A.; Neary, D.; Snowden, J. S.; et al.
<x xml:space="preserve">Abstract</x> Y. S. Davidson, A. C. Robinson, Q. Hu, M. Mishra, A. Baborie, E. Jaros, R. H. Perry, N. J. Cairns, A. Richardson, A. Gerhard, D. Neary, J. S. Snowden, E. H. Bigio and D. M. A. Mann (2013) Neuropathology and Applied Neurobiology39, 157–165 Nuclear carrier and RNA‐binding proteins in frontotemporal lobar degeneration associated with fused in sarcoma (FUS) pathological changes Aims: We aimed to investigate the role of the nuclear carrier and binding proteins, transportin 1 (TRN1) and transportin 2 (TRN2), TATA‐binding protein‐associated factor 15 (TAF15) and Ewing's sarcoma protein (EWS) in inclusion body formation in cases of frontotemporal lobar degeneration (FTLD) associated with fused in sarcoma protein (FTLD‐FUS). Methods: Eight cases of FTLD‐FUS (five cases of atypical FTLD‐U, two of neuronal intermediate filament inclusion body disease and one of basophilic inclusion body disease) were immunostained for FUS, TRN1, TRN2, TAF15 and EWS. Ten cases of FTLD associated with TDP‐43 inclusions served as reference cases. Results: The inclusion bodies in FTLD‐FUS contained TRN1 and TAF15 and, to a lesser extent, EWS, but not TRN2. The patterns of immunostaining for TRN1 and TAF15 were very similar to that of FUS. None of these proteins was associated with tau or TDP‐43 aggregations in FTLD. Conclusions: Data suggest that FUS, TRN1 and TAF15 may participate in a functional pathway in an interdependent way, and imply that the function of TDP‐43 may not necessarily be in parallel with, or complementary to, that of FUS, despite each protein sharing many similar structural elements.